Colonial Legacy: French Retirees in Nha Trang, Vietnam Today. Issue 3 (1st December 2021) - Raffin, Anne
Abstract: Based on interviews with thirty-eight French retirees living in the seaside city of Nha Trang, Vietnam, this article queries their reasons for migrating and investigates how they make sense of their life abroad. I consider Vietnam's historical connection with the French empire as a possible component of lifestyle migration and meaning. This small-scale study indicates that colonial memories and historical ties between France and Vietnam do influence many interviewees' choice of place of retirement. However, for most, the personal and social amenities afforded by a tropical life in the present tend to eventually displace such memories.